On the Denseness of One Set of Series - Laurinčikas, A. (Nonlinear Analysis: Modelling and Control, 2001)
In the paper the denseness of the set of all convergent series related to a class of multiplicative functions is obtained.
Keywords: function of exponential type; multiplicative function; space of analytic functions